Alienation in the Runaways (A Novel by Fatima Bhutto): A Psychoanalytical Reasoning for Fundamentalism and Radicalization - Ayesha Rabbi*; Saima Hassan; Shehla Anwer Kurd (Al-Qanṭara, 2023)
The aim of the paper is to discuss how Young Adults are suffering from alienation in the contemporary post 9/11 situation resulting in their involvement in terrorist activities. The work is contextualized by referring to Fatima Bhutto’s novel The Runaways (2019). Fundamentalism and Radicalism are often associated with terrorism having religious origin. This research intends to explore the possible reasons behind young people and gun violence. The theme of alienation is further explored from a psychoanalytical perspective drawing from Lacan’s concept of other. The nuanced study of the novel will help understand the psychological condition of the young people caught in extremism and radicalism. Keywords: Alienation, Identity, Radicalism, Fundamentalism, Lacan, The Runaways